PENGARUH SENAM OTAK TERHADAP KEMAMPUAN MEMAINKAN BOLA VOLI DAN BOLA TENIS DENGAN BERBAGAI JENIS GERAKAN SISWA KELAS V SD NEGERI PETIRREJO KECAMATAN NGADIREJO KABUPATEN TEMANGGUNG TAHUN AJARAN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
This study aims to find out how to influence the Brain Gym to the Ability to Playing Volleyball and Tennis Ball With Different Types of Class V Students Movement Elementary School of Petirrejo Sub-district Ngadirejo District Temanggung Academic Year 2013/2014. The method used in this study is a quantitative method. In the implementation consists of three stages: pre-test, treatment and post test. Based on the results of the pretest obtained the highest score is 7 and lowest score 2. Based on the data obtained posttest scores highest at 13 and lowest scores 4. Conclusion, that the provision of treatment of brain gym to the ability to play volleyball and tennis balls with different types of movements Elementary School Fifth Grade Students Petirrejo has a positive and significant effect, so it would be better if the provision of permanent brain gym done regularly.